Management of Developing Interactive Multimedia-Based Arabic Teaching Materials: Enhancing Learning for Diverse Students at Indonesian Islamic Universities - Muflihah; Hanifah, Umi; Thoha, Mohammad; Haji Abdullah, Hajah Rafidah binti (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study also examines the management of interactive multimedia-based Arabic language teaching development. It evaluates the effectiveness of the teaching material, which uses interactive multimedia-based, in enhancing the learning process of the Arabic language in Islamic universities in Indonesia. Given students' diverse backgrounds, interactive multimedia has proven effective in promoting engagement and independent language acquisition. Pre-test and post-test results from UIN A, UIN B, and IAIN C show significant differences between the results of the experimental group and the results of the control groups. At UIN A (t-count 16.83 > t-table 1.684), UIN B (t-count 14.278 > t-table 1.682), and IAIN C (t-count 9.34 > t-table 1.682), students in the experimental groups demonstrated substantial improvement compared to the control groups. These findings confirm that interactive multimedia effectively enhances student engagement and learning outcomes in Arabic language programs at Islamic universities in Indonesia.